Transport of Amino Acids Across the Blood-Brain Barrier - Zaragozá, Rosa (Frontiers in Physiology, 2020)
The blood-brain-barrier (BBB) present in brain capillaries, constitutes an essential barrier mechanism for normal functioning and development of the brain. The presence of tight junctions between adjacent endothelial cells restricts permeability and movement of molecules between extracellular fluid and plasma. The protein complexes that control cell-cell attachment also polarize cellular membrane, so that it can be divided into luminal (blood-facing) and abluminal (brain) sides, and each solute that enters/leaves the brain must cross both membranes. Several AA transport systems with different distribution in both sides of the BBB have been described. In a broad sense, at least five different systems of facilitative transporters, and all of them are found in the luminal membrane. Some of these transporters are very specific for a small group of substrates, and are located exclusively on the luminal side of the BBB. However, the two major facilitative carriers, system L and system y+, are located in both membranes although asymmetrically. The position of these Na+-independent transporters ensures AA availability into the brain and also its bidirectional transport across the endothelia cells. On the other hand, there are several Na+-dependent transport systems that will transport AAs against its concentration gradient together with the movement of Na+ ions. The majority of these active tranporters are present exclusively at the abluminal membrane, being responsible of amino acid efflux from the brain into the endothelial cells. Since those are Na+-coupled, the sodium pump Na+/K+-ATPase is also highly expressed in this abluminal side of the BBB. Once inside the cell the facilitative transporters located in the luminal membranes will mediate export from endotehial cell to blood. In summary, the polarized distribution of those transport systems between the luminal and abluminal membranes, and the fact that more than one transporter may carry the same substrate ensures supply and excretion of AAs in and out of the brain, controlling its homeostasis and proper function.